Hidden, Unwanted or Simply Forgotten? A Bioarchaeological Profile of the Subačius Street 41 Population - Kozakaitė, Justina; Miliauskienė, Žydrūnė; Brindzaitė, Rūta (Archaeologia Lituana, 2019)
In 2014–2015, an unknown 16th–17th-century cemetery was discovered at the Subačius Street 41 plot in Vilnius. The uncovered human remains are considered to be one of the most abundant and best-preserved anthropological material in the territory of present-day Vilnius. Paradoxically, historical sources do not mention this burial site, although the abundance of the interred individuals does not imply an accidental burial, but perhaps a functioning cemetery for some time. In such exceptional cases, the only source of information is the synthesis of archaeological and anthropological research data. This article presents preliminary results and a brief overview of bioarchaeological (demographic, paleopathological, and dental research, height reconstruction) investigation. A total of 151 individuals were studied, with almost half (45%) of them consisting of children. Almost 60% of the individuals had one or more pathological lesions. The average height of male individuals was estimated 168.2 cm, the average height of females was 157.8 cm. The aim of this study can be defined as twofold: an attempt to identify the people buried outside the city walls and systematize for the first time the bioarchaeological data of one-out-of-many Vilnius populations. Currently, the Subačius Street 41 population does not resemble a typical urban community, so the study itself is the first attempt to reveal the osteobiography of these 16th–17th century Vilnius residents.